Normative Data of the Trail Making Test Among Urban Community-Dwelling Older Adults in Japan - Suzuki, Hiroyuki; Sakuma, Naoko; Kobayashi, Momoko; Ogawa, Susumu; Inagaki, Hiroki; Edahiro, Ayako; Ura, Chiaki; Sugiyama, Mika; Miyamae, Fumiko; Watanabe, Yutaka; Shinkai, Shoji; Awata, Shuichi (Frontiers in Aging Neuroscience, 2022)
Introduction: Population aging is likely to increase the number of people with dementia living in urban areas. The Trail Making Test (TMT) is widely used as a cognitive task to measure attention and executive function among older adults. Normative data from a sample of community-dwelling older adults are required to evaluate the executive function of this population. The purpose of this study was to examine the Trail Making Test completion rate and completion time among urban community-dwelling older adults in Japan. Methods: A survey was conducted at a local venue or during a home visit (n=1,966). Cognitive tests were conducted as a part of the survey, and TMT Parts A (TMT-A) and B (TMT-B) were completed after the completion of the Japanese version of the Mini-Mental State Examination (MMSE-J). Testers recorded TMT completion status, completion time, and the number of errors observed. Results: In the TMT-A, 1,913 (99.5%) participants understood the instructions, and 1,904 (99.1%) participants completed the task within the time limit of 240 s. In the TMT-B, 1,839 (95.9%) participants understood the instructions, and 1,584 (82.6%) participants completed the task within the time limit of 300 s. The completion rate of TMT-B was 90.2% and 41.8% for participants with an MMSE-J score of >23 points and ≦23 points, respectively. Results of multiple regression analyses showed that age, education, and the MMSE-J score were associated with completion time in both TMTs. Conclusions: In both TMTs, completion time was associated with age, education, and general cognitive function. However, not all participants completed the TMT-B, and the completion rate was relatively low among participants with low MMSE-J scores. These findings may help interpret future TMT assessments.